2021
DOI: 10.3390/s21124093
|View full text |Cite
|
Sign up to set email alerts
|

Smart-Contract Aware Ethereum and Client-Fog-Cloud Healthcare System

Abstract: The Internet of Medical Things (IoMT) is increasingly being used for healthcare purposes. IoMT enables many sensors to collect patient data from various locations and send it to a distributed hospital for further study. IoMT provides patients with a variety of paid programmes to help them keep track of their health problems. However, the current system services are expensive, and offloaded data in the healthcare network are insecure. The research develops a new, cost-effective and stable IoMT framework based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 29 publications
0
48
0
Order By: Relevance
“…To the best of our knowledge, a hybrid workload-enabled and secure healthcare monitoring sensing framework in a distributed fog cloud network has not been studied yet. The considered problem and system in the present study differ from existing works [1, 2,18,22,[28][29][30][31] in the following way. The proposed work considers the hybrid workloads such as workflow and the fine-grained model and the proposed mathematical model, whereas the study devises the functions and virtual machine aware fog cloud network which was not considered in the existing works.…”
Section: Related Workmentioning
confidence: 97%
See 4 more Smart Citations
“…To the best of our knowledge, a hybrid workload-enabled and secure healthcare monitoring sensing framework in a distributed fog cloud network has not been studied yet. The considered problem and system in the present study differ from existing works [1, 2,18,22,[28][29][30][31] in the following way. The proposed work considers the hybrid workloads such as workflow and the fine-grained model and the proposed mathematical model, whereas the study devises the functions and virtual machine aware fog cloud network which was not considered in the existing works.…”
Section: Related Workmentioning
confidence: 97%
“…The objective is to offload healthcare data with their deadlines on the cloud servers. The study of [2] suggested IoMT-based coarse-grained healthcare workloads, with resource constraints and the programming aware constraint method on latency optimal edge nodes. The study implemented a DES security mechanism for offloaded workloads in the system.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations